Effect of silvopastoral systems with integrated forest species from the Peruvian tropics on the soil chemical properties - Saucedo Uriarte, José Américo; Ampuero-Trigoso, Gustavo; Pasquel-Barzola, Kinthia K.; Quispe Ccasa, Hurley Abel; Chuquimia-Valdez, Dixie S.; Arévalo-Aranda, Yuri G. (De Gruyter, 2025)
Vegetation and trees in Amazonian ecosystems influence soil chemistry. Understanding these effects is essential for selecting the right tree species in silvopastoral systems to promote soil conservation. The objective of the study was to evaluate the effect of different silvopastoral systems (SPS) on the soil chemical properties within a livestock system. The research was developed at the Estación Experimental Agraria El Porvenir in San Martín Department, Peru, which is characterized by a humid tropical climate, with an annual temperature of 33°C, humidity levels between 70 and 80%, and precipitation of 1,225 mm. Six SPS [Bolaina (Guazuma crinita Mart.), Teak (Tectona grandis L.), an arboretum, Pucaquiro (Sickingia tinctoria Schult.), Quinilla (Manilkara bidentata A. DC.), and a natural forest - NF] and two sampling depths were compared, with two replicas for each. The main effect showed that the Quinilla SPS was higher in pH (p < 0.05), while the Quinilla SPS, Pucaquiro SPS, and NF stood out in K⁺ and Ca²+ (p < 0.05). Organic matter (OM) and nitrogen content were higher at the 0–10 cm depth; however, there was an interactive effect on EC, OM, and nitrogen in the Quinilla SPS (p < 0.05). A total of 65.31% of the variance is explained by exchangeable cations (47.98%) and OM and nitrogen (17.33%). The planting of M. bidentata A. DC. and S. tinctoria Schult. trees in SPS could enhance soil nutrient availability similarly to natural forests, although the age of systems may influence these outcomes.